Literacy Tourism Revolution: The Role of Technology in Increasing Students' Interest in Reading and Learning - Wibowo, Wahyu (RADINKA JAYA UTAMA PUBLISHER, 2025)
Literacy has a crucial role in the education and development of a country, but the level of literacy in Indonesia is still relatively low. One of the innovations to increase students' interest in reading is literacy tourism, which is now developing from conventional methods to technology-based approaches. This research aims to analyze the role of technology in revolutionizing literacy tourism and its impact on students' interest in reading and learning. With a literature review method, this study examines various academic sources related to literacy tourism, educational technology, and its implementation challenges. The results of the study show that the use of technology such as digital libraries, e-books, augmented reality (AR), and virtual reality (VR) can increase students' interest in reading and understanding through more interactive learning experiences. However, challenges such as limited infrastructure, uneven access to technology, and lack of teacher training are still the main obstacles. Therefore, synergy between the government, schools, and the private sector is needed to support the integration of technology in literacy tourism. With an inclusive approach, technology-based literacy tourism has the potential to strengthen literacy culture in schools and create a more critical and innovative generation.